2019
DOI: 10.1007/s11156-019-00834-3
|View full text |Cite
|
Sign up to set email alerts
|

Foreign institutional ownership and demand for accounting conservatism: evidence from an emerging market

Abstract: This study investigates how foreign institutional ownership interacts with accounting conservatism in an emerging market setting. We posit that weak investor protection and a high degree of information asymmetry between insiders and outside investors increase demand for conservative reporting in firms operating in emerging markets. Foreign investors in this setting have informational disadvantages relative to their domestic peers and have difficulties in getting access to data. Using a sample of Turkish firms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 67 publications
2
14
0
3
Order By: Relevance
“…For example, in KSA, as Naif and Ali (2019), the capital market 'Tadawul' is considered one of the good markets for FI, but many issues are pending and not implemented to attract more foreign investors. This result is supported by An (2019) which found no relationship between FI and EQ-CON, but it is not in line with Khalil et al (2020) which found that conservatism practices are attractive practices for foreign investors. In general, foreign investors prefer to invest in firms audited by the big 4, have less risk, and are small in size as conservatism is low.…”
Section: Measuring and Analysis Of Eq-con And Fimentioning
confidence: 77%
See 3 more Smart Citations
“…For example, in KSA, as Naif and Ali (2019), the capital market 'Tadawul' is considered one of the good markets for FI, but many issues are pending and not implemented to attract more foreign investors. This result is supported by An (2019) which found no relationship between FI and EQ-CON, but it is not in line with Khalil et al (2020) which found that conservatism practices are attractive practices for foreign investors. In general, foreign investors prefer to invest in firms audited by the big 4, have less risk, and are small in size as conservatism is low.…”
Section: Measuring and Analysis Of Eq-con And Fimentioning
confidence: 77%
“…Shubita (2015) concluded that income smoothing improves EQ in the GCC countries. With respect to the relationship between EQ and foreign investors, Khalil et al (2020) found that foreign investors demand conservative reporting of earnings. Ferreira et al (2017) reached the same conclusion regarding the foreign investors' preference for conservative reporting of earnings because they have informational disadvantage.…”
Section: Conservatismmentioning
confidence: 99%
See 2 more Smart Citations
“…For all these reasons, new technologies pose challenges both for researchers and for teachers and professionals of the accounting practice, in order to form a broad and flexible vision of accounting, which allows offering a useful and reliable service in the context of permanent transformation. The use of new tools or technological supports in accounting has inherent risks in the efficient management of organizations and their link with the different markets through the dissemination of accounting information [12][13][14].…”
Section: Introductionmentioning
confidence: 99%